Geostrophic circulation between the Costa Rica Dome and Central America - Brenes, C.L. (2008)
The geostrophic circulation between the Costa Rica Dome and Central America is described from CTD observations collected in two surveys: (a) The Wet Cruise in September–October 1993, and the Jet Cruise in February–March 1994. Poleward coastal flow was present on both occasions, but the transition from flow around the dome to the poleward Costa Rica Coastal Current flow was quite tortuous because of the presence of mesoscale eddies. In particular, a warm anticyclonic eddy was found off the Gulf of Fonseca during both cruises, at an almost identical position and with similar dimensions (150 m deep, 250 km in diameter) and surface speed (0.5 m s 1 ). In the Gulf of Panama, poleward flow was also observed, weaker in February–March 1994 than in September–October 1993, when it penetrated to 600 m depth and transported 8.5 Sv. In September–October 1993, the current between the dome and the coast was mostly 100 m deep and weak ( 0.15 m s 1 ), although in its southern side it was deeper ( 450 m) and faster at 0.3 m s 1 . The poleward transport between the dome and the coast was 7 Sv. In February–March 1994 the Costa Rica Dome was a closed ring adjacent to the continental shelf, 500 km in diameter, at least 400 m deep, had geostrophic surface speeds 0.25 m s 1 , and subsurface maximum speed (0.15–0.20 m s 1 ) at 180 m depth; the associated uplift of the isotherms was 150 m. The flow in the south part of the dome splits into two branches, the weakest one going around the dome and the strongest one continuing east and turning south before reaching the Gulf of Panama. r 2008 Elsevier Ltd. All rights reserved.